A new species of Synotaxus and the first chromosomal study on Synotaxidae, presenting a rare XY sex chromosome system in spiders (Araneae, Araneoidea) - Souza, Lucas Henrique Bonfim; Brescovit, Antonio Domingos; Araujo, Douglas (Zootaxa, 2017)
Studies on spider chromosomes are very scarce, with 44 spider families without any cytogenetically analyzed species. Nevertheless, chromosomal characteristics can be useful for species delimitation, such as the sex chromosome system (SCS), which is particularly diverse in spiders. In this study, we describe Synotaxus jaraguari n. sp., based on male and female specimens from midwestern Brazil. This species has a distinctive “horn” in the male ocular area and seems related to a group of species that includes Synotaxus monocerus (Caporiacco, 1947), S. itabaiana Santos & Rheims, 2005 and S. siolli Santos & Rheims, 2005. We also present the first karyotype study on Synotaxidae. The mitotic and meiotic cells of S. jaraguari n. sp. revealed 2n♂ = 22 + XY and 2n♀ = 22 + XX telocentric chromosomes. This is the ninth spider species with a XY/XX SCS, which is extremely rare in the group.